Shiga toxin-1 Decreases Endothelial Cell Tissue Factor Pathway Inhibitor Not Co-localized with Tissue Factor on the Cell Membrane. Issue 6 (June 2015) - Grabowski, Eric F.; Liu, Bohan; Gerace, Matthew R.; Kushak, Rafail I.; Ingelfinger, Julie R.
Highlights: Shiga toxin-1 + TNFα enhances procoagulant tissue factor (TF) on endothelial cells. This results from a decrease in "free" cell surface TF pathway inhibitor (TFPI). The enhanced procoagulant TF is not due to an increase in "free" TF.